The value of transferable skills - Sgobbi, F. (2016)
This paper assesses the extent of inter-firm transferability for the skills developed by white-collar employees in the Portuguese retail banking sector. Assuming that employers will be willing to reward productive skills only, we measure skill transferability as the wage differential between firm switchers and firm stayers. Based on Quadros de Pessoal, a longitudinal archive of linked employer-employee data on the Portuguese labour market, our results support the hypothesis of significant inter-firm and inter-industry skill transferability. Difference-in-differences estimates with propensity score matching show that, on average, firm switchers benefit from a wage premium compared to firm stayers. However, when accounting for the destination sector the observed wage premium quickly drops with the distance from the banking industry.